DENTAL CARE FOR CHILDREN AFTER REPLANTATION OF AVULSED PERMANENT INCISORS - Rossitza Kabaktchieva; Natalia Gateva; Angela Gusiyska; Pavel Stanimirov; Nina Milcheva (Peytchinski Publishing, 2016)
The diagnosis avulsion of permanent tooth/teeth is an emergency situation which has special requirements in respect of proper storage of the avulsed tooth, the need of urgent medical/dental care, time past till replantation and splinting, the need for endodontic treatment and long term follow up period. Those clinical actions depend on three groups: parents/people who are with the child in the moment when trauma happens and give the first aid; dental specialist- surgeon who replants the tooth/teeth; dental specialist- endodontist who takes care of the endodontic treatment and the long period after treatment for follow up and observation of the replanted teeth. The aim of the paper is to present the dental postoperative care in a couple of cases of children with trauma and replanted avulsed permanent incisors. Material and methods: We present four clinical cases of children who get 6 permanent upper incisors replanted. Replantation is made by the oral surgeon. Treatment and observation after replantation are made by dental specialists of pediatric dentistry and conservative dentistry. All 4 cases get 3 years follow up period. Results: After replantation of 2 central incisors with complete root development (first clinical case) the left one has developed a resorption of the root but the right one is in a stable condition. Replantation of 3 teeth with incomplete root development (second and third clinical cases) where the patients refer to specialized surgical care less than 60 minutes after injury and store the teeth in different ways lead to different clinical results. In the case of avulsed upper right incisor (second case), it is stored in milk and we observe revascularization followed by partial root canal obliteration. The tooth is scheduled for endodontic treatment. In the case of upper central incisors, both kept dry till replantation in the alveolus filled up with substitute bone, we observe fast root resorption which going to lead to early tooth loss. After replantation of the first upper incisor with open apex, stored in physiological solution for 5 hours and with delayed endodontic treatment (forth case) healing process is stable and the prognosis is good. Follow up period for all the replanted teeth has continued. Conclusion: The presented clinical cases show that there is a lack of dental teams for complex treatment of children with avulsed teeth in Bulgaria. Dental specialists have no good information about recommended by IADT protocols (www.iadt-dentaltrauma.org), for the treatment of teeth undergoes avulsion during childhood. Parents of these children have no proper information about how to store the teeth which are avulsed and found immediately after trauma.